2023
DOI: 10.3390/toxics11020165
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Changes in Selected Volatile Organic Compounds (VOCs) and Associations with Health Risk Assessments in Industrial Areas during the COVID-19 Pandemic

Abstract: During the COVID-19 pandemic, governments in many countries worldwide, including India, imposed several restriction measures, including lockdowns, to prevent the spread of the infection. COVID-19 lockdowns led to a reduction in gaseous and particulate pollutants in ambient air. In the present study, we investigated the substantial changes in selected volatile organic compounds (VOCs) after the outbreak of the coronavirus pandemic and associations with health risk assessments in industrial areas. VOC data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 58 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Levels of total volatile organic compounds (TVOCs) at the industrial areas investigated ranged between 0.05 and 4.821 mg/m 3 (Table 2). The range of total volatile organic compounds obtained is higher than 32.81 -47.22 µg/m 3 reported in Delhi, India by Singh et al [50]. The mean values of TVOCs at COPC, APC, and MPC were higher than the recommended limit for unpolluted air by FEPA [37], whereas the values obtained at BPC and CCMY were within the limit.…”
Section: Levels Of Air Pollutants At the Industrial Areas Examined An...mentioning
confidence: 57%
“…Levels of total volatile organic compounds (TVOCs) at the industrial areas investigated ranged between 0.05 and 4.821 mg/m 3 (Table 2). The range of total volatile organic compounds obtained is higher than 32.81 -47.22 µg/m 3 reported in Delhi, India by Singh et al [50]. The mean values of TVOCs at COPC, APC, and MPC were higher than the recommended limit for unpolluted air by FEPA [37], whereas the values obtained at BPC and CCMY were within the limit.…”
Section: Levels Of Air Pollutants At the Industrial Areas Examined An...mentioning
confidence: 57%
“…More studies based on complete datasets are required to understand the magnitude of the impact of the elevated benzene concentrations, especially in the petrochemical areas. For example, in Delhi, India, the lifetime cancer risk values for males and females were higher during the lockdown period compared to the pre- and post-lockdown periods due to longer exposure time to increase the production of plastic and resin manufacturing units during the pandemic period [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged exposure to VOCs can be fatal (Elena et al, 2021). A number of studies have shown that cardiovascular and respiratory diseases are largely associated with individual VOCs (Singh al, 2023). Oxidation of VOCs results in plentiful production of organic acids, which in turn initiates aerosol nucleation (Guo et al, 2020).…”
Section: Effects Of Vocs On Human's Health and The Environmentmentioning
confidence: 99%